Analisis Kinerja Inspektorat Daerah Kabupaten Klaten dalam Melakukan Pengawasan Internal pada Tahun 2023 - Fajar, Malik; Rahmah, Fania Jamilatul; Atika, Sitti Nurmahida; Saputro, Riro Adnan; Darmawan, Ivan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine and analyze the performance of the Regional Inspectorate in carrying out its duties and functions to supervise the performance of national civil servants within the scope of the Klaten Regional Government, to determine the suitability between the work plans that have been determined and their realization, a comparison between the realization of performance in 2023 and the realization of performance in previous years, as well as what factors constitute obstacles for the inspectorate in carrying out its duties and factors for its success. The method used in this research is the literature study method in which data is collected through sources such as books, journal articles, and supervisory report documents as well as other documents sourced from the internet. The results obtained are that supervision of the Klaten Regency regional inspectorate has increased from year to year, but in its implementation it has not yet reached a very good level, because there are still many things that have not been realized, both in terms of supervision, monitoring and evaluation, up to the supervision program which has only been implemented half of the 140 monitoring program planned with funds of 2.7 trillion.